Verification of communication protocols in web services : model-checking service compositions - Mukherjee, Anshuman; Tari, Zahir; Bertok, Peter, 1952- (Hoboken, New Jersey : Wiley, 2014)
'Provides implementation details of each networking type to help readers to be able to set up Sensor networks in their related job fields'--
Keywords: Web services -- Testing; Computer network protocols